Sufficient and Necessary Center Conditions for the Poincaré Systems P(2,2n)(n≤5) - Jinya Xu; Zhengyi Lu (Journal of Applied Mathematics)
We obtain sufficient and necessary center conditions for the Poincaré system P(2,2n)(n≤5). The necessity of the condition is derived from the first 2n focal values by symbolic computation with Maple, and the sufficiency is proved by Volokitin's method.